CEO Political Leanings and Store‐Level Economic Activity during the COVID‐19 Crisis: Effects on Shareholder Value and Public Health - BIZJAK, JOHN M.; KALPATHY, SWAMINATHAN L.; MIHOV, VASSIL T.; REN, JUE (Journal of Finance, 2022)
Maintaining economic output during the COVID-19 pandemic results in benefits for firm shareholders but comes at a potential cost to public health. Using store-level data, we examine how a CEO's political leaning impacts this trade-off. We document that firms with a Republican-leaning CEO experience a relative increase in store visits compared to firms with a Democratic-leaning CEO. The increase in store visits is associated with higher sales and positive abnormal stock returns. However, we also document higher COVID-19 transmission rates and more employee safety complaints in communities where establishments with higher store traffic are managed by a Republican-leaning CEO.